Business Statesman or Shareholder Advocate? CEO Responsible Leadership Styles and the Micro‐Foundations of Political CSR - Maak, Thomas; Pless, Nicola M.; Voegtlin, Christian (Journal of Management Studies, 2016)
ABSTRACT In this article we pursue two objectives. First, we refine the concept of responsible leadership from an upper echelon perspective by exploring two distinct styles (instrumental and integrative) and thereby further developing the understanding of the newly emerging integrative style. Second, we propose a framework that examines the micro‐foundations of political corporate social responsibility (CSR). We explicate how the political CSR engagement of organizations (in social innovation and multi‐stakeholder initiatives) is influenced by responsible leadership styles and posit that most CEOs tend to espouse either instrumental or integrative responsible leadership approaches, based on perceived moral obligations toward shareholders or stakeholders. We examine the moderating effects of societal‐ and organizational‐level factors (such as power distance and corporate governance), and individual‐level influences (such as cognitive and social complexity). We discuss both approaches with respect to their effectiveness in dealing with political CSR challenges in a complex environment and conclude that an instrumental responsible leadership style may be effective in relatively stable settings with strong institutional arrangements, while the complex and unstable context of a post‐national constellation with weak institutions calls for an integrative responsible leadership style. The latter can be expected to be more effective in dealing with political CSR challenges in a global world, contributing to closing governance gaps and producing sustainable outcomes for societies.